Knowing when to discontinue Temozolomide therapy in responding aggressive pituitary tumors and carcinomas: a systematic review and Padua (Italy) case series. Issue 2 (4th March 2023) - Padovan, Marta; Cerretti, Giulia; Caccese, Mario; Barbot, Mattia; Bergo, Eleonora; Occhi, Gianluca; Scaroni, Carla; Lombardi, Giuseppe; Ceccato, Filippo
ABSTRACT: Introduction: Pituitary adenomas can show a tendency to grow, despite multimodal treatment. Temozolomide (TMZ) has been used in the last 15 years in patients with aggressive pituitary tumors. TMZ requires a careful balance of different expertise, especially for selection criteria. Areas covered: We conducted: (1) a systematic review of the published literature from 2006 to 2022, collecting only cases with a complete description of patient follow-up after TMZ discontinuation; (2) a description of all patients with aggressive pituitary adenoma or carcinoma treated in Padua (Italy). Expert opinion: There is considerable heterogeneity in the literature: TMZ cycles duration ranged from 3 to 47 months; the follow-up time after TMZ discontinuation ranged from 4 to 91 months (mean 24 months, median 18 months), at least a stable disease has been reported in 75% of patients after a mean 13 months (range 3–47 months, median 10 months). The Padua (Italy) cohort reflects the literature. Future directions to explore are to understand the pathophysiological mechanism of TMZ resistance escape, to develop predicting factors to TMZ treatment (especially through the delineation of the underlying transformation processes), and to further expand the therapeutic applications of TMZ (as neoadjuvant, combined with radiotherapy).